Rapid land use conversion in the Cerrado has affected water transparency in a hotspot of ecotourism, Bonito, Brazil. (13th September 2022) - Chiaravalloti, Rafael Morais; Tomas, Walfrido Moraes; Uezu, Alexandre; Shirai, Henrique Yugo; Guaraldo, Eliane; Aoki, Camila; de Arruda Botelho, Maria Tereza; Salvadori, Juliane Ferreira
Background: Brazil is the largest exporter of soybeans worldwide. Albeit its economic importance, soybean expansion has led to important land use and land cover changes. In this paper, we evaluate the impact of soybean expansion on ecotourism, using as a case study of the Prata River (Bonito), Brazil; tourist destination where over 30, 000 tourists per year came to float in crystal waters. Methods: We first evaluated land cover and land use change in the region between 2010 and 2020, checking how and where soybean plantations have expanded. Second, based on monthly data of water transparency of the Prata River, Bonito, we created five possible models considering monthly rainfall and three categories of soybean expansion (slow, rapid and medium). The models were tested through generalized linear regression analysis and ranked through AIC and AIC weight. Results: Our results show that soybean expanded from occupying 4% of the river basin in 2010 to 23% in 2020, expanding mostly over pasture areas (31%) and native vegetation (12.9%). We also showed that while soybean plantation was expanding rapid between 2014 and 2016, it played a significant role in increasing the number of days the water in the Prata River was classified as very turbid. Conclusion: Our results emphasize the need for soybean expansion planning, considering better management of the soil (non-tilling), common agreements between different stakeholders and the scale up of initiatives that are already in place in the region (e.g. planning of the locations of legal reserves in a way that complement the environmental protection areas (e.g. Águas de Bonito), seting aside of conservation areas ("Área Prioritária Banhados") and payment for ecosystem service schemes) . Implications for conservation: Our research shows the importance of considering the different impacts soybean may have on the landscape. We present clear paths to reduce possible economic and environmental impacts, and present the importance to scale up innitiatives that are already in place in the region, such as payment for ecosystem services schemes and protection of watersheds.